Union Wage Gap in the U.S. Construction Sector: 1983–2007. Issue 3 (19th June 2013) - Bilginsoy, Cihan
<x xml:space="preserve">Abstract</x> Wage gap decomposition shows that declining union power was the principal force behind the shrinking union wage premium in the U.S. construction industry between the 1980s and the 2000s. This decline was largely offset by changes in returns to workforce attributes and workforce compositions. Without these moderating effects, the decline in the wage gap would have been twice as large (in log points). The patterns were similar in the basic and mechanical trades, but magnitudes of change were larger in the latter.